DAMPAK UTANG LUAR NEGERI INDONESIA DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Hairunnisa (LA RIBA: Jurnal Perbankan Syariah, 2019)
Economic development is a process that must be carried out by the state to increase the welfare of the entire nation. Without the support of productive economic resources, economic development cannot be carried out properly. Therefore, the government carried out a series of policies, one of which was implementing a foreign debt policy. The decline in government External Debt was influenced by global sentiment as a result of the widespread COVID-19 pandemic, which prompted capital outflows from the domestic Government Securities (SBN) market. Government External Debt is managed to support government spending in priority sectors in an effort to encourage economic growth and increase public welfare. The government's external debt aims to support economic development and growth, which has a positive impact in the form of overcoming an increase in production (GDP), expanding employment opportunities and improving the balance of payments. However, the negative impact if the debt is not used improperly, it will threaten the macroeconomic stability of the country. The view of the Islamic economist group that rejects this budget deficit assumes that interest regardless of any motive, production, consumption and however large / high / multiplied / or low, is still seen as usury. Meanwhile, according to the second view, regarding foreign debt, the deficit budget can be used in an Islamic country with several conditions.